Pengembangan Multimedia Interaktif Tema Diriku Untuk Siswa Kelas 1 Sekolah Dasar - Yunita Sari; Jupriyanto Jupriyanto (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to develop interactive multimedia products on the theme of myself, this development is motivated by the lack of students' understanding of the material and the lack of learning media that can be used by teachers in the learning process, causing low student achievement and less motivated in learning. The exist-ence of this interactive multimedia development can help students in the learning process. This study uses the ADDIE development model, the stages are Analysis, De-sign, Development, Implementation, and Evaluation. Based on these five stages the development of interactive multimedia obtains research results, including: (1) The feasibility of interactive multimedia obtained from the validation results of 3 validators obtained an average result of 0.82 with a very valid category. (2) The practicality of interactive multimedia gets a percentage of 90% with a very good category from the teacher's response and student responses get a percentage of 91% with a very good category. Based on these results interactive multimedia can be said to be feasible and practical for grade 1 elementary school students.